Revisiting Roles, Redefining Growth: State and Market in Economic Transformation - Alifia, Indi; Mukhtar, Ramadhan Arifin; Zumara, Zumara (Ta'amul: Journal of Islamic Economics, 2024)
Economic transformation is a multifaceted process that can no longer be comprehensively understood through macro-structural models alone. In many national contexts, the boundaries between the roles of the state and the market are increasingly blurred, leading to ambiguity in understanding their respective contributions. This study addresses the problem of unclear functional dynamics between public and private actors in driving economic change. The primary objective is to explore how both the state and the private sector contribute to economic transformation through a qualitative lens. Employing in-depth interviews, document analysis, and case studies as data collection techniques, this research adopts a constructivist qualitative approach to interpret the evolving relationships and institutional behaviors shaping development processes. The findings suggest that economic transformation is not solely the result of top-down policy design or spontaneous market evolution, but rather an outcome of continuous negotiation, contestation, and adaptation between state and market actors. Furthermore, the study reveals the importance of narratives, power asymmetries, and informal institutional arrangements in influencing developmental trajectories. These insights contribute to expanding the theoretical landscape of development studies by highlighting the co-productive nature of state–market interactions. Practically, the research underscores the need for more inclusive and dialogical policymaking processes that foster collaboration across sectors. Ultimately, this study calls for a rethinking of developmental roles—not as fixed categories—but as fluid, contested, and context-dependent constructs that evolve with socio-political and economic change.